A familial amyotrophic lateral sclerosis pedigree discordant for a novel p.Glu46Asp heterozygous OPTN variant and the p.Ala5Val heterozygous SOD1 missense mutation. (May 2020) - Canosa, Antonio; Grassano, Maurizio; Barberis, Marco; Brunetti, Maura; Manera, Umberto; Vasta, Rosario; Cammarosano, Stefania; De Marco, Giovanni; Calvo, Andrea; Chiò, Adriano; Moglia, Cristina
Highlights: Multiple variants in ALS-related genes are detectable in Familial ALS (FALS). FALS cases without the pathogenic mutation found in the kindred have been reported. Our FALS case did not show the p.A5V SOD1 mutation found in his affected relatives. Our FALS case carried a novel OPTN variant of uncertain significance (VUS). Discordant genetic results and VUS complicate genetic counselling in FALS. Abstract: About 10% of Amyotrophic Lateral Sclerosis (ALS) cases are familial (FALS), mainly related to mutations in C9ORF72, SOD1, TARDBP, and FUS genes. Recent data revealed the presence of multiple variants in ALS-associated genes in FALS in excess of what is to be expected by chance. FALS patients not carrying a pathogenic genetic mutation detected in their kindred have been reported. We report a FALS case, who did not carry the p.Ala5Val heterozygous SOD1 mutation that had been detected in other affected subjects of his kindred. He underwent Next-Generation Sequencing, revealing a novel p.Glu46Asp heterozygous OPTN variant of uncertain significance (VUS). Discordant genetic test results in FALS cases within the same family and the detection of variants of uncertain significance increase the complexities of genetic counselling.